(3EOGQI GdHfhc JbdjOjI GdeGVj hGdcJQhfjI GdeSJbHds - (3CMeO eMeO(B, (3Zfjes ((3GdEScfOQjI(B:s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY,s, 2007)
(3jVe EOGQI GdHfhc, gjcd GdLgGR GdeUQaj, GdeHGOF GdMGceI dCYeGd GdHfhc, EOGQI GdNOeGJ GdeUQajI, EOGQI ehGQO GdHfhc, EOGQI fTGW JhXja CehGd GdHfhcs
(3HHdjhZQGajG(B: (3U(B.151s
Keywords: (3GdEOGQI GdeGdjIs; (3GdHfhcs